Environmental sustainability strategies and impacts: A case study in Northport, Klang Malaysia - Muhammad Nasrullah, Mohd Gapar (2015)
Environmental sustainability, a focal point for the government of Malaysia, is also important in developing business sustainability for businesses including ports. Following this, the research objectives of this study were threefold: 1) investigating the impact of strategies implemented by Northport, Klang in order to be environmentally sustainable, 2) ascertaining the priorities of these strategies and 3) determining the barriers or challenges faced by the port in its efforts of implementing the strategies. Using qualitative research design, data was collected through semistructured interview with the officers in charge of environment at the Northport, Klang, Malaysia. Findings indicate that strategies implemented by the port have been successful in their efforts to reduce emission and improve air quality, a big step in being environmentally sustainable. Several criteria were used to prioritize the strategies, chief among them being implementation cost and time, maintenance cost and reduction of carbon emission. In terms of priority, the first strategy was operational strategy in terms of vessel speed reduction initiative, followed by infrastructure and equipment strategy with equipment and engine replacement and emission control technology and lastly, image improvement strategy with the initiative of the implementation of green building. The biggest barrier in implementing these strategies was cost.